PTSD symptoms amongst Icelandic police officers : the effect of social support and resilience - Stefanía Hildur Ásmundsdóttir 1993- (2017)
This study was conducted to examine PTSD rates among Icelandic police officers. All police officers in Iceland were offered to participate through an online questionnaire. The final sample consisted of 93 participants, and the response rate was about 15% of participants within the population. There were 76 male participants and 17 female participants. The aim of the study was threefold. First, to examine PTSD symptoms among Icelandic police officers. Results showed that 15% of participants met diagnosis criteria for having PTSD symptoms. Secondly, to examine the protective role of social support and resilience in PTSD among Icelandic police officers. According to the results, there was a significant negative correlation between social support and PTSD symptoms and between resilience and PTSD. Results also showed that those above the median on social support reported fewer PTSD symptoms and those above the median on resilience reported fewer PTSD symptoms. The third purpose of the study was to examine the combined effects of social support and resilience on PTSD. The results showed that the interaction effect between social support and resilience on PTSD symptoms was not significant. Keywords: police officers, first responders, PTSD, post-traumatic stress disorder, social support, resilience Rannsóknin var framkvæmd til að kanna einkenni áfallastreituröskunar meðal lögreglumanna á Íslandi. Öllum lögreglumönnum á Íslandi var boðið að taka þátt í gegnum spurningalista á netinu. Úrtakið innihélt 93 þátttakendur, sem jafngildir um það bil 15% af þýðinu. Alls voru 76 karlkyns þátttakendur og 17 kvenkyns þátttakendur. Tilgangur rannsóknarinnar var þríþættur. Í fyrsta lagi að kanna algengi áfallastreituröskunareinkenna meðal íslenskra lögreglumanna, þar sem það hefur ekki verið gert hingað til. Niðurstöður sýndu að 15% þátttakenda voru með einkenni áfallastreituröskunar samkvæmt greiningarviðmiðum. Í öðru lagi, að kanna verndandi áhrif félagslegs stuðnings og seiglu þegar kemur að áfallastreituröskun meðal ...